Photoluminescence characterization of AlN nanowhiskers - Vokhmintsev, A.S.; Weinstein, I.A.; Chaikin, D.V.; Spiridonov, D.M.; Afonin, Yu.D. (Functional Materials, 2014)
Photoluminescence (PL) properties of synthesized Al-rich nanowhiskers with diameter 60±20 nm and bulk AlN single crystals were compared at the room temperature. It was found that PL spectra for AlN nanowhiskers were characterized by three components of the Gaussian shape with maximum energy 3.16, 2.90, and 2.55 eV and halfwidth 0.7, 0.4, and 0.7 eV, respectively. It was shown that the same bands - 3.2 and 2.6 eV - were observed in luminescence of the bulk and nanostructured samples. The registered emissions were attributed to electron-optical transitions between donor levels of the ON-, VN-centers and acceptor states of the CN-centers and (ON-VAl)-complexes.